PAWNING GOLD IN ISLAMIC BANKS FROM THE PERSPECTIVE OF ISLAMIC LAW AS THE LIVING LAW IN INDONESIA - Fariana, Andi; Amelia, Mega Putri; Hartati, Ralang (Proceeding International Seminar of Islamic Studies, 2023)
There are three areas of law that live and grow (the living law) in Indonesia, which are Customary Law, Islamic Law, and Western Law. These three areas of law are the main material for the national legal system. Islamic law which is based on the Qur'an and hadith has perfectly regulated all aspects of life including muamalah matters, and one part of muamalah activity is pawning. The rapid development of Islamic Banks is a challenge to itself to make the actors in this industry need to innovate in creating banking products, but of course, it must be in accordance with Islamic principles. This research was conducted by tracing the various legal bases for the application of gold pawning to Islamic banks and the practice model so that this research was carried out in a normative juridical manner using a statute approach and comparative law studies as well as complementing it with the results of interviews regarding the practice of gold pawning on Islamic banks. The results of the study shows that the values of Islamic law, which are the living law after going through legal politics, have been transformed into and become part of the national legal system. Therefore, their practice is in accordance with sharia principles.